Metaphoric and metonymic expressions of ‘Red’ in Song Poetry / Liu Yiting - Liu , Yiting (2022)
In this study color terms about ‘red’ are selected from 300 Song Lyrics. Metonymy and metaphorical expression of this color term in 300 Song Lyrics would be classified, analyzed and discuss the cognitive mechanism behind these expressions. To find out what are the metonymic and metaphorical expressions of ‘red’ in ancient poetry (Song Lyrics). The study found four metonymic expressions that are commonly used in Song Lyrics, including (1) Red for spring, (2) Red for red flower, (3) Red for beautiful lady and (4) Red for red cosmetics, and four metaphoric expressions that are commonly used in Song Lyrics which are (1) Youth and vitality is red, (2) Power and wealth is red, (3) Mundane world is red, and (4) Prosperity is red. Besides, the method and mechanism by which figurative expressions of red terms are formed in the first place. By studying the color "red" in Song Lyrics, not only may native speakers become more aware of their cultural symbols, but non-native speakers and translators can gain a better understanding of the Chinese language and culture as well. Meanwhile, it is suggested that future researchers can be performing additional in-depth research on other color terms in order to further their understanding, and researchers are encouraged to look at the metaphor from both a synchronic and a diachronic perspective.